Social learning and adolescent deviance abstention: Toward understanding the reasons for initiating, quitting, and avoiding drugs - Winfree, Latham T. (Journal of quantitative criminology, 1993)
Tests of theories that attempt to explain why individuals currently use drugs are widespread; however, the theoretical examinations of abstention from drugs and the cessation of their use are rare. For its part, social learning theory has been supported consistently in its delineation of the process by which substance use is learned. We propose that cessation and abstention are also learned behavior. Using logistic regression analysis, we examine the ability of social learning variables to distinguish among abstainers, current users, and former users of illicit drugs within a sample of 1688 middle- and high-school students in two widely separated nonurban communities. Results indicate that social learning variables clearly distinguish abstainers from current users but are less able to distinguish former users and current users or former users from abstainers. The theoretical, research, and policy implications of these findings are examined in detail.